Spark of Light: Short Stories by Women Writers of Odisha - Edited by Valerie Henitiuk and Supriya Kar (Mingling Voices, 2016)
Spark of Light is a diverse collection of short stories by women writers from the Indian province of Odisha. Originally written in Odia and dating from the late nineteenth century to the present, these stories offer a multiplicity of voices-some sentimental and melodramatic, others rebellious and bold-and capture the predicament of characters who often live on the margins of society. From a spectrum of viewpoints, writing styles, and motifs, the stories included here provide examples of the great richness of Odishan literary culture. In the often shadowy and grim world depicted in this collection, themes of class, poverty, violence, and family are developed. Together they form a critique of social mores and illuminate the difficult lives of the subaltern in Odisha society. The work of these authors contributes to an ongoing dialogue concerning the challenges, hardships, joys, and successes experienced by women around the world. In these provocative explorations of the short-story form, we discover the voices of these rarely heard women.